An Investigation into Alcohol Use among Female Undergraduate Psychology Students at the University of Limpopo, South Africa. (2nd January 2017) - Govender, I.; Nel, K. A.; Sibuyi, X. M.
ABSTRACT: This paper investigates alcohol use among female undergraduate students at the University of Limpopo, South Africa using a cross-sectional survey. The sample was 700 female undergraduate psychology students. The self-administered questionnaire consisted of demographic information, the Michigan Alcohol Screening Test – revised, five questions from the Protection Motivation Theory, and the Alcohol Use Disorders Identification self-report test. One hundred and thirty questionnaires were completed (19%) of the first-year students, 27.1 percent had attended an Alcoholics Anonymous meeting, 22.9 percent had lost a job, 16.7 percent have liver problems, 18.8 percent had been arrested for drinking and driving, and twenty-five percent had been in trouble at the university. There was a statistically significant difference ( p = 0.00) between respondents across different years of study for these results. First-year respondents had the most alcohol-related problems. Alcohol use in a significant proportion of female students is concerning. Many participants had not considered stopping using alcohol and would not change their drinking behaviour.